White matter microstructural damage and depressive symptoms in patients with mild cognitive impairment and cerebral small vessel disease: the VMCI‐Tuscany Study. (21st October 2015) - Pasi, Marco; Poggesi, Anna; Salvadori, Emilia; Diciotti, Stefano; Ciolli, Laura; Del Bene, Alessandra; Marini, Sandro; Nannucci, Serena; Pescini, Francesca; Valenti, Raffaella; Ginestroni, Andrea; Toschi, Nicola; et al.
Abstract : Background and purpose: Disruption of cortical‐subcortical circuits related to small vessel disease (SVD) may predispose to depression in the elderly. We aimed to determine the independent association between white matter (WM) microstructural damage, evaluated with diffusion tensor imaging (DTI), and depressive symptoms in a cohort of elderly subjects with mild cognitive impairment (MCI) and SVD. Methods: The vascular mild cognitive impairment (VMCI)‐Tuscany Study is an observational multicentric longitudinal study that enrolled patients with MCI and moderate to severe degrees of WM hyperintensities on MRI. Lacunar infarcts, cortical atrophy, medial temporal lobe atrophy, microbleeds, and DTI‐derived indices (mean diffusivity, MD and fractional anisotropy, FA) were evaluated on baseline MRI. Geriatric Depression Scale (GDS) (score 0–15) was used to assess depressive symptoms. An extensive neuropsychological battery, Instrumental Activities of Daily Living scale, and the Short Physical Performance Battery were used for cognitive, functional, and motor assessments, respectively. Results: Seventy‐six patients (mean age: 75.1 ± 6.8 years) were included. Univariate analyses showed a significant association between GDS score and both DTI‐derived indices (MD: r  = 0.307, p  = 0.007; FA: r  = −0.245; p  = 0.033). The association remained significant after adjustment for age, WM hyperintensities severity, global cognitive, functional and motor performances, and antidepressant therapy (MD: r  = 0.361, p  = 0.002; FA: r  = −0.277; p  = 0.021). Conclusions: These results outline the presence of an association between WM microstructural damage and depressive symptoms in MCI patients with SVD. This relationship does not seem to be mediated by disability, cognitive, and motor impairment, thus supporting the vascular depression hypothesis. Copyright © 2015 John Wiley & Sons, Ltd.